Nephrometry scores: can preoperative assessment of sectional imaging really mirror intraoperative renal tumor anatomy? - Egen, Luisa; Kowalewski, Karl-Friedrich; Riffel, Philipp; Honeck, Patrick; Kriegmair, Maximilian (Urologia internationalis, 2021)
Introduction: To compare RENAL, preoperative aspects and dimensions used for an anatomical (PADUA) classification, and Mayo Adhesive Probability (MAP) scores with the respective intraoperative findings and surgeon’s assessment in predicting surgical outcome of patients undergoing partial nephrectomy. Methods: Data of 150 eligible patients treated at the University Medical Center Mannheim between 2016 and 2018 were analyzed. Tumors were radiologically and intraoperatively assessed by PADUA, RENAL, and MAP scores and surgeon’s assessment. Correlations and regression models were created to predict ischemia time (IT), major complications, and Trifecta (negative surgical margin, IT < 25 min, and absence of major complications). Results: There were strong correlations between radiological and intraoperative RENAL (r = 0.68; p < 0.001) and PADUA scores (r = 0.72; p < 0.001). Radiological RENAL, PADUA, and MAP scores and surgeon’s assessment were independent predictors of Trifecta (OR = 0.71, p = 0.015; OR = 0.77, p = 0.035; OR = 0.65, p = 0.012; OR = 0.40, p = 0.005, respectively). IT showed significant associations with radiological RENAL, PADUA, and surgeon’s assessment (OR = 1.41, p = 0.033; OR = 1.34, p = 0.044; OR = 3.04, p = 0.003, respectively). MAP score proved as only independent predictor of major complications (OR = 2.12, p = 0.002). Conclusion: Radiologically and intraoperatively assessed scores correlated well with each other. Intraoperative nephrometry did not outperform radiological scores in predicting outcome confirming the value of the existing systems. MAP score correlates well with surgeon’s assessment of perirenal fat and major complications underlining the importance of perirenal fat characteristics.